SISTEM DAN PROSEDUR PENDAFTARAN HAJI DI KEMENTERIAN HAJI DAN UMROH KABUPATEN MANDAILING NATAL - Rigon Hasibuan; Ahmad Syahril; Yusni Zakiah Lubis; Ismi Zakiyah Dly; Nila Rahmadani; Anggita Dewi Harahap; Nur Ainun Lubis; Desi Safitri; Siti Suaibah; Muniroh; Amiruddin; Nurul Sakinah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Hajj pilgrimage is the fifth pillar of Islam and is obligatory for all Muslims who are able. The high level of public interest makes the Hajj registration process crucial and must be carried out in an orderly and transparent manner. This study aims to describe the Hajj registration system and procedures at the Ministry of Hajj and Umrah Office in Mandailing Natal Regency and the role of students in the Hajj registration process during the field experience practicum (PPL). The method used is descriptive qualitative with a participatory approach through the Field Experience Practicum (PPL) activities. The results show that Hajj registration is carried out in two stages, namely at the bank and at the Ministry of Hajj and Umrah office using the SISKOHAT application. This system helps improve the effectiveness and transparency of services, although there are still obstacles such as a lack of public understanding and limited use of technology.